The formation and development of biomechanics in Sytenko Institute of Spine and Joint Pathology (to the 125th anniversary of M. I. Sytenko’s birth) - Tyazhelov, Olexiy; Miteleva, Zoya; Karpinsky, Mykhaylo; Subbota, Igor; Karpinska, Olena (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2011)
Landmarks in the formation and development of the first Soviet biomechanics laboratory are elucidated in a historical sketch. The part of biomechanical studies in the development of new methods for treating diseases and injuries of the locomotor apparatus is shown. The article lists a range of tasks of biomechanics as a science, and the laboratory in particular, for improving the efficacy of treatment of patients of the orthopaedic-traumatological type.